PEMANFAATAN MEDIA SOSIAL INSTAGRAM AKUN @VAPORMXPKU DALAM MENINGKATKAN PROMOSI PENJUALAN - Fadli, Rian; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Utilizing social media instagram in making sales is not an easy thing, given the seller does not face each other in making sales transactions. An @vapormaxpku account is an account that sells electric cigarettes on instagram social media. The misappropriation of social instagram matures has made sales increase. This shows that social media instagram offers a large enough business opportunity. This study aims to determine the use of instagram as a medium of communication in increasing sales promotion vapormaxpku, the use of instagram as a medium of marketing transactions in increasing sales Vapormaxpku as well as the use of instagram as Business media Vapormaxpku account. This study used qualitative research methods. Research subjects consist of Owner Vapormaxpku, 1 person Employee, 1 persons Customer using instagram and follow Vapormaxpku account selected by using purposive technique. Data collection is done through interview, observation and documentation. To test the validity of data writer used extension method of participation and triangulation. The results of this study indicate that (1) Instagram utilization as a communication medium is vapormax utilizing social media to communicate with the public, customers and business associates. Vapormax Makes social media instagram as a means of promoting Vapormaxpku so as to reach the public more broadly. (2) Instagram utilization as marketing transaction medium. Instagram usage can advertise for free and does not need to cost this way more effectively for marketing of the product, and simplify the introduction of the brand directly that makes consumers curious about the product, the process of marketing instagram has interesting features and can affect its users in the application and make it easier for its marketing. and (3) Instagram utilization as a business medium. The use of instagram can be used as a means of delivering information on vapormaxpku products to consumers, from which the information will produce a useful interaction to attract the interest of consumers and prospective consumers. Keywords: instagram usage, social media, vapormaxpku